The impact of natural virtual environments on emotion elicitation: a state-of-the-art review - Marocco, Silvia; Vitale, Valeria; Grossi, Elena; Giffi, Veronica; Santoriello, Morena (Frontiers in Virtual Reality, 2025)
Natural environments have been widely recognized for their calming effects on individuals. However, access to such restorative environments can be limited by various circumstances. In these cases, Virtual Reality can be beneficial, as recent studies have shown that immersion in virtual natural environments has effects comparable to those of real nature. Various characteristics of natural environments can potentially influence the benefits they provide to humans. Additionally, the design of VR interventions can impact the experience and emotional response. This review aims to survey the current state of knowledge on the impact of virtual natural environments on emotion elicitation, addressing the types of interventions used in past studies, the variety of natural environments employed, and their differential impacts on emotional valence and arousal. This analysis shows how longer sessions, especially those involving interactive elements such as hand gestures, proved to be the most effective in enhancing emotional and physiological benefits. Among the various types of natural environments used, green spaces, particularly virtual forests, were the most frequently studied and showed consistent effectiveness in both reducing arousal and eliciting positive emotions. These findings can inform the development of new VR interventions designed to foster restoration and enhance positive emotional responses.